2019
DOI: 10.1016/j.jchf.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Medical Management of Heart Failure With Reduced Ejection Fraction in Patients With Advanced Renal Disease

Abstract: Large randomized clinical trials (RCT) supporting guidelines for the management of HFrEF have typically excluded patients with advanced CKD. Patients with concomitant advanced CKD and HFrEF experience poor cardiovascular outcomes and mortality relative to either disease in isolation and have been shown to consistently receive lower rates of HFrEF guideline-directed medical therapy (GDMT). In this review, we evaluate recent evidence for the use of GDMT in patients with HFrEF and advanced CKD approaching dialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Cumulative studies have shown a bi‐directional relationship between CKD and CVD, and the development of either disease may accelerate the progression of the other. Approximately 10% of patients with heart failure (HF) have a severe reduction of estimated glomerular filtration rate (eGFR), and patients with CKD are prone to develop CVD 3 . Mechanisms, including hypervolemia, inflammation and endothelial dysfunction, worsen the course of both CKD and HF 4 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Cumulative studies have shown a bi‐directional relationship between CKD and CVD, and the development of either disease may accelerate the progression of the other. Approximately 10% of patients with heart failure (HF) have a severe reduction of estimated glomerular filtration rate (eGFR), and patients with CKD are prone to develop CVD 3 . Mechanisms, including hypervolemia, inflammation and endothelial dysfunction, worsen the course of both CKD and HF 4 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Several randomized controlled trials (RCTs) have revealed that renin‐angiotensin‐aldosterone system inhibition (RASi) can decrease the risk of cardiovascular events, HF hospitalizations and mortality 3 . Nevertheless, renal adverse events are observed frequently during clinical practice, when treating patients with angiotensin‐converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) 5 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Despite the well-established benefits of MRAs in HFrEF, just as with RAS inhibitors and ARNIs, there is concern for hyperkalemia in patients with advanced CKD (Hein et al, 2019). The SPin-D trial randomized 129 patients on maintenance HD to placebo or spironolactone 12.5 mg, 25 mg, or 50 mg daily.…”
Section: Mineralocorticoid Receptor Antagonists (Mras)mentioning
confidence: 99%
“…To identify critical practical barriers and gaps in care and knowledge, several scientific statements have been developed to summarize the current findings in areas with incomplete evidence. 5,6 Unfortunately, these efforts have demonstrated that a lack of evidence in this field is pervasive, with inconclusive evidence regarding important outcomes, such as the quality of life, physical function, and maintenance of independence, in patients with advanced age and concomitant disease, making it difficult to identify appropriate interventions. Accordingly, there is a critical need for more practical guidance in areas with incomplete evidence to transform clinical guideline recommendations into clinically actionable information.…”
Section: Introductionmentioning
confidence: 99%